2017
DOI: 10.1097/sla.0000000000002382
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Molecular Imaging Combined With Positron Emission Tomography Improves Surgical Management of Peripheral Malignant Pulmonary Nodules

Abstract: These data suggest that combining IMI with PET may provide superior oncologic outcomes for patients with resectable lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 26 publications
2
52
0
Order By: Relevance
“…Our inclusion criteria required subjects be deemed surgical candidates prior to enrollment, which may artificially inflate some of the test characteristics of TumorGlow® by increasing pre-test probabilities. We accept this limitation as we envision this technology serving as an adjunct to, not a replacement for, current diagnostics and therapeutics (20). Secondly, determining an actual false-negative rate is challenging.…”
Section: Commentmentioning
confidence: 99%
“…Our inclusion criteria required subjects be deemed surgical candidates prior to enrollment, which may artificially inflate some of the test characteristics of TumorGlow® by increasing pre-test probabilities. We accept this limitation as we envision this technology serving as an adjunct to, not a replacement for, current diagnostics and therapeutics (20). Secondly, determining an actual false-negative rate is challenging.…”
Section: Commentmentioning
confidence: 99%
“…The first in-human intraoperative FR-targeted fluorescence imaging study demonstrated that FR-targeted imaging can be a valuable tool for intraoperatively detecting and quantifying tumor growth and spread. 7 Previous studies have suggested that FR overexpression in lung cancer is correlated with cell proliferation. 8,9 Folate receptors promote tumor growth, probably through increasing folate uptake from serum or interaction with associated signaling molecules.…”
mentioning
confidence: 99%
“…Therefore, FRs and folate play a vital role in cancer generation and development. The first in‐human intraoperative FR‐targeted fluorescence imaging study demonstrated that FR‐targeted imaging can be a valuable tool for intraoperatively detecting and quantifying tumor growth and spread …”
mentioning
confidence: 99%
“…Moreover, a folate-targeted conjugate of the highly cytotoxic drug, tubulysin B, has been shown in clinical trials of lung and ovarian cancer patients to display little off-target toxicity (43), suggesting that any normal cell that expresses a folate receptor is either not readily accessed or not damaged by the folate-linked drug. Because a folate-NIR dye conjugate currently in late-stage clinical trials for fluorescence-guided surgery of lung and ovarian cancer has demonstrated 98% sensitivity and 96% positive-predictive value with little if any toxicity (44), the folate receptor would seem at this juncture to qualify for possible further evaluation as a tumor antigen for CAR T-cell therapies. Similarly, many mRNA and IHC expression studies (26) together with toxicity data on PSMA-targeted radiotherapeutic agents in clinical trials for metastatic castration-resistant prostate cancer (23) suggest that PSMA may also constitute an attractive candidate for CAR T-cell applications.…”
Section: Discussionmentioning
confidence: 99%